Hyperbaric oxygen therapy in idiopathic sudden sensorineural hearing loss (ISSNHL) in association with combined treatment - Holy, R; Navara, M; Dosel, P; Fundova, P; Prazenica, P; Hahn, A (Undersea & hyperbaric medicine, 2011)
The main basic effect of hyperbaric oxygenation (HBO2) on the human body, in our study, was an increased partial pressure of oxygen resulting from an increased amount of oxygen dissolved in plasma. Thus the plasma can become capable of carrying enough oxygen to meet the needs of the body's tissues. From 1 January 2004 to 31 December 2007, a total of 61 patients (62 ears) received medical treatment at the ENT clinic of the 3rd Faculty of Medicine, Charles University, and at the Central Military Hospital in Prague. Treatment consisted of a combination of vasodilatation infusion treatment and HBO2 therapy. The results were evaluated in a retrospective study. The overall percentage of patients showing improvement was 59.7%. However, for those patients who started HBO2 treatment within 10 days of onset, complete recovery, or significant improvement was noted in 65.9%. In contrast, patients who started treatment after 10 days of onset, improvement was noted in only 38.9%. NMR examination revealed that two patients had vestibular schwannoma (also known as acoustic neuroma).
Keywords: vinca alkaloidy; dospělí; Vasodilation; Pentoxifylline; Female; kombinovaná terapie; Audiometry; vazodilatancia; Hearing Loss, Sensorineural; Adult; hyperbarická oxygenace; výsledek terapie; ženské pohlaví; mladý dospělý; Partial Pressure; Time Factors; časové faktory; Vinca Alkaloids; lidé; pentoxifylin; vazodilatace; glukokortikoidy; Glucocorticoids; Treatment Outcome; Middle Aged; Vasodilator Agents; retrospektivní studie; Male; Combined Modality Therapy; parciální tlak; Aged; Methylprednisolone; Oxygen; Young Adult; methylprednisolon; lidé středního věku; senioři; mužské pohlaví; percepční nedoslýchavost; audiometrie; Hyperbaric Oxygenation; Retrospective Studies; Hearing Loss, Sudden; kyslík; náhlá nedoslýchavost; Humans